Reciprocality in Papuan Malay - Sawaki, Yusuf (UI Scholars Hub, 2021)
Reciprocality, also known as reciprocal situation or reciprocal constructions, constitutes an expression which describes both the forms and meaning of an activity embodying a mutual relation. Papuan Malay, a pidginized lingua franca in Western New Guinea, has three types of constructions expressing reciprocality: lexical reciprocals, prototypical syntactic reciprocals with the baku construction, and syntactic reciprocals with the discontinuous satu... satu construction. Some additional constructions are considered to be reciprocal-like. These reciprocal constructions vary in their argument structure and valence operations. In argument structure, most constructions allow two kinds of argument structure: Type 1, which takes only a subject argument, and Type 2, which takes both a subject and object, and follows the basic SVO word order. However, the object in the Type 2 construction becomes oblique-like, indicating reduced transitivity in order to accommodate the concept of mutual relation. In valence operations, reciprocals can undergo both valence decreasing and valence increasing operations. In addition, some reciprocal constructions require subject and object to be syntactically retained, even though semantically they represent the same agent-patient/goal mutual relation.